Where did all the remittances go? Understanding the impact of remittances on consumption patterns in rural China - Yu Zhu; Zhongmin Wu; Liquan Peng; Laiyun Sheng (University of Kent, Department of Economics, 2009)
We focus on the impact of migrants' remittances on consumption patterns in rural China, allowing for endogeneity of remittances and county fixed-effects. We find that the marginal propensity to consume out of remittances is close to unity, which is far greater than that out of non-migrant earnings or farm income. These findings imply that rural households take remittances as permanent income and are consistent with the prevalence of circular and repeat migration which is largely caused by the combination of the restrictive hukou (household registration) system and the rigid land tenure system in China.
Keywords: D12; D13; J61; R23; 330; rural-urban migration; remittances; consumption patterns; fixed-effect instrumental-variables estimation; Landflucht; Rücküberweisung (Migranten); Konsumentenverhalten; Ländlicher Raum; China